The Lokpal and Lokayukta Act of 2013 : A Comprehensive Analysis of its Legislative Journey, Salient Features, and Effectiveness in Combating Corruption in India - Manjeet Pal; Dr. Kulwant Singh (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The Lokpal and Lokayukta Act of 2013, enacted by the Indian Parliament, aims to establish an independent anti-corruption ombudsman to investigate allegations of corruption against public officials. This paper critically evaluates the Act, tracing its legislative journey, analyzing its key provisions, and assessing its potential effectiveness. Despite significant public support and legislative effort, the Act faces challenges in implementation and potential loopholes. This study delves into the historical context, legislative processes, and the critical features of the Act while examining its strengths and weaknesses. The analysis underscores the need for robust enforcement mechanisms and suggests amendments for enhancing the Act’s efficacy in the fight against corruption.